DISPARITAS USIA MINIMAL PERKAWINAN DALAM KOMPILASI HUKUM ISLAM PERSPEKTIF TEORI BATAS MAṢLAḤAH SA’ĪD RAMAḌĀN AL-BŪṬI - Hilmy, Ahmad Arif Masdar (JURNAL ISLAM NUSANTARA, 2019)
This research is a document research that discussed and analyzed about the disparity in the minimum age limit of marriage in Article 15 of the Indonesian Islamic Law by using the theory of maá¹£laá¸¥ah Sa'Ä«d Ramaá¸n al-BÅ«á¹i. This research became urgent in order to increase khazanah of science which is progressive and also opened insight into the opportunities for new thoughts, regarding the absence of rules in the disparity of minimum age limits of marriage for men and women in Islamic law. The data of this study were collected through the documentation method. After that, the reading was done on the text (text reading) and then the texts were analyzed. The result showed that the disparity in the minimum age limit of marriage in Article 15 KHI was based on consideration of the benefit of the family and household. The conclusion of the author's brief research was that the substance contained in Article 15 of the KHI concerning about the disparity in the minimum age limit of marriage for men and women included the benefits of parenting (mental, spiritual, financial and physical), social balance, and responsibility of marriage. The disparity in the minimum age limit of marriage in Article 15 of the KHI was a benefit if it was reviewed by using the theory maá¹£laá¸¥ah from Sa'Ä«d Ramaá¸Än al-BÅ«á¹i, because it had fulfilled five conditions, which were maslaá¸¥ah must be within the scope of the Shari'ah objectives, does not contradict to The Qur'an, does not contradict with the Sunnah, does not contradict with Qiyas, and does not contradict with the more urgent maá¹£laá¸¥ah.